Sustainable construction and demolition waste management in Malaysia: current issues - Abolghasemi, Maryam (Faculty of Management, Universiti Teknologi Malaysia, 2017)
Construction and Demolition Waste (CDW) is a deep concern for most developing countries due to its harmful impact on the environment, society, and economy. Sustainable CDW is helped to maintain the stability between the environment, social and economic aspects through several ways, including the implementation of waste management techniques. The effectiveness of implementing sustainable CDW management in this kind of economy, however, is incredibly limited due to numerous barriers. Therefore, this paper attempts to offer insights into the management practices of CDW by identifying several issues that hinder the management of sustainable CDW in Malaysia. The data collection approach includes a thorough review of all sustainable CDW related academic papers, official reports and statistics, as well as government legislations. The finding includes the issues and challenges of sustainable management of CDW in Malaysia with the aim of demonstrating the current challenges related to sustainability of CDW, which are eventually summarized as the eight most important barriers to implemented CDW management in the Malaysian construction industry. The findings of this paper will contribute substantial evidences to both academicians and practitioners towards better management and planning of the policies for CDW in the Malaysian construction industry.